9
$\begingroup$

$$ \lim_{x\to0}\frac{\cos x-\cos (3x)}{\sin (3x^2)-\sin (x^2)} $$

Is there a simple way of finding the limit?
I know the long one: rewrite it as $$ -\lim_{x\to 0}\frac{\cos x-\cos(3x)}{\sin(3x^2)}\cdot\frac{1}{1-\dfrac{\sin(3x^2)}{\sin(x^2)}} $$ and then find both limits in separately applying L'Hospital's rule several times. The answer is $2$.

$\endgroup$
12
$\begingroup$

By standard limits

  • $\frac{\sin x}x \to 1$

  • $\frac{1-\cos x}{x^2} \to \frac12$

we have that

$$\frac{\cos x-\cos(3x)}{\sin(3x^2)-\sin(x^2)}=\frac{\frac{\cos x-1+1- \cos(3x)}{x^2}} {\frac{\sin(3x^2)-\sin(x^2)}{x^2}}=\frac{-\frac{1-\cos x}{x^2}+9\frac{1- \cos(3x)}{(3x)^2}} {3\frac{\sin(3x^2)}{3x^2}-\frac{\sin(x^2)}{x^2}}\to\frac{-\frac12+\frac92}{3-1}=2$$

$\endgroup$
8
$\begingroup$

Hint: Use $$\sin 3a=3\sin a-4\sin^3a$$ $$\cos 3a=4\cos^3a-3\cos a$$ Edit: After substutution it is $$\lim_{x\to0}\frac{2\cos x\sin^2x}{\sin x^2\cos2x^2}=2$$

$\endgroup$
  • 1
    $\begingroup$ Now the votes are balanced! $\endgroup$ – Nosrati Jul 30 '18 at 21:01
7
$\begingroup$

Hint: Use the factorisation formula $$\cos a -\cos b =-2\sin{a+b\over 2}\sin{a-b\over 2}$$ and $$\sin a -\sin b =2\sin{a-b\over 2}\cos{a+b\over 2}$$

$$ \lim_{x\to0}\frac{\cos x-\cos (3x)}{\sin (3x^2)-\sin (x^2)} = \lim_{x\to0}\frac{2\color{red}{\sin 2x}\cdot \color{green}{\sin x}\cdot\color{blue}{x^2}}{\color{blue}{\sin (x^2)}\cos (2x^2)\cdot\color{red}{2x}\cdot \color{green}{x}} =2$$

$\endgroup$
7
$\begingroup$

I would use Taylor polynomials at order $2$.

$$\frac{\cos x-\cos (3x)}{\sin (3x^2)-\sin (x^2)}=\frac{1-\frac{x^2}{2}-\left(1-\frac{(3x)^2}{2}\right)+o(x^2)}{3x^2-x^2+o(x^2)}=\frac{4x^2+o(x^2)}{2x^2+o(x^2)}=2+o(1) $$

$\endgroup$
  • 5
    $\begingroup$ Minor nitpick: if you're going to use $o$-notation, you should do it throughout the whole calculation, and not only at the end. Otherwise the notation would be inconsistent. $\endgroup$ – AccidentalFourierTransform Jul 30 '18 at 20:55
  • $\begingroup$ @gimusi Indeed I made an error : not dividing the o() by $x^2$. Thanks for noting. I corrected. $\endgroup$ – mathcounterexamples.net Jul 31 '18 at 10:41
  • $\begingroup$ @mathcounterexamples.net Well done! You are welcome, Bye. $\endgroup$ – gimusi Jul 31 '18 at 13:45
4
$\begingroup$

Simply use Taylor' formula ultimately at order $2$ to find equivalents: near $0$, $$\cos u=1-\frac{u^2}2+o(u^2),\qquad \sin u=u+o(u)$$ so \begin{align} \cos x-\cos 3x&=1-\frac{x^2}2+o(x^2)-\Bigl(1-\frac{9x^2}2+o(x^2)\Bigr)= 4x^2+o(x^2)\\ \sin 3x^2-\sin x^2&=3x^2+o(x^2)-\bigl(\sin x^2+o(x^2)\bigr)=2x^2+o(x^2). \end{align} Thus the numerator is equivalent to $4x^2$, the denominator to $2x^2$, whence $$\frac{\cos x-\cos 3x}{\sin 3x^2-\sin x^2}\sim_0\frac{4x^2}{2x^2}=2.$$

$\endgroup$
2
$\begingroup$

Use the Maclaurin series $$\cos x = 1-1/2 \; x^2+1/24 \; x^4 +O(x^6)$$ $$\cos 3x = 1-9/2 \; x^2+27/8 \; x^4 +O(x^6)$$ $$\sin x^2 = x^2-1/6\; x^6+O(x^8)$$ $$\sin 3x^2 = 3x^2-9/2 \; x^6+O(x^8)$$ then quotient is $$\frac{-1/2 + 9/2}{3-1} + O(x^2)$$ and therefore the limit is 2.

$\endgroup$
  • $\begingroup$ To simplify, It suffices to expand to the second order terms $x^2$. $\endgroup$ – gimusi Jul 30 '18 at 20:38
2
$\begingroup$

Using l'Hôpital directly is very awkward.

The denominator has $x^2$, but it is immediate that $$ \lim_{t\to0}\frac{\sin3t-\sin t}{t}=3-1=2 $$ Consequently, also $$ \lim_{x\to0}\frac{\sin(3x^2)-\sin(x^2)}{2x^2}=1 $$ Good! Now we can write our limit in the form $$ \lim_{x\to0}\frac{\cos x-\cos 3x}{2x^2}\frac{2x^2}{\sin(3x^2)-\sin(x^2)} $$ The first fraction can be easily dealt with: $$ \lim_{x\to0}\frac{\cos x-\cos 3x}{2x^2}= \lim_{x\to0}\frac{3\sin3x-\sin x}{4x}= \lim_{x\to0}\frac{9\cos3x-\cos x}{4}=2 $$


For completeness, a much simpler strategy is using Taylor expansion: $$ \frac{\cos x-\cos3x}{\sin(3x^2)-\sin(x^2)}= \frac{1-x^2/2-1+(3x)^2/2+o(x^2)}{3x^2-x^2+o(x^2)}= \frac{4+o(1)}{2+o(1)} $$ so the limit is $2$.

$\endgroup$
  • $\begingroup$ Is this correct $o(1)→0$? $\endgroup$ – Takahiro Waki Jul 31 '18 at 0:55
  • 1
    $\begingroup$ @TakahiroWaki Yes of course, recall that by definition $o(1)=1\cdot \omega(x)$ with $\omega(x)\to 0$. $\endgroup$ – gimusi Jul 31 '18 at 5:39
0
$\begingroup$

$$ \cos x-\cos(3x) = \cos x\left(\sin^2x+3\sin^2 x\right) $$

then

$$ \frac{\cos x-\cos (3x)}{\sin (3x^2)-\sin (x^2)} = \frac{x^2}{x^2}\cos x\left(\frac{\sin^2x+3\sin^2 x}{\sin (3x^2)-\sin (x^2)}\right)=\cos x\left(\frac{\left(\frac{\sin x}{x}\right)^2+3\left(\frac{\sin x}{x}\right)^2}{\frac{3\sin(3x^2)}{3x^2}-\frac{\sin (x^2)}{x^2}}\right) $$

hence

$$ \lim_{x\to 0}=\cos x\left(\frac{\left(\frac{\sin x}{x}\right)^2+3\left(\frac{\sin x}{x}\right)^2}{\frac{3\sin(3x^2)}{3x^2}-\frac{\sin (x^2)}{x^2}}\right) = 1\cdot\left(\frac{1+3}{3-1}\right) = 2 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.